Men and Women; An Analysis of the Difference Status of Men and Women Especially in the Asian Regions - Prashobh, Karunakaran (International Research Journals, 2014)
This paper aims at resolving the mass murder of female babies or fetuses in India, China and elsewhere. The number of female babies or children killed in India and China alone is running at over 220 million over this generation alone. The only thing humans at large can do about this appalling genocide (the killing of babies without the Y gene) is to foster equal status of men and women and bring about men of quality who respects women’s equality. This genocide has been covered up with names like infanticide but it is actually the worst genocide in the history of earth. The word genocide has been adopted by United Nations to have legal consequences in January 1951. Once a situation categorized as genocide, countries are compelled to take action. 140 nations have rectified this convention so far. This United Nations charter came about due to the vigorous campaign by a lawyer named Raphael Lemkin to prevent the horrors of the holocaust from ever happening again.